Comunidades de leveduras associadas a cactáceas de ecossistemas de cerrado e restinga - Larissa Falabella Daher de Freitas (2014)
Cacti necrotic tissues form an ecological system in which cactophilic yeasts depend on insect vectors for dispersion, and these vectors in turn use these microorganisms as food supply, given that they represent a source of vitamins, sterols and proteins. Furthermore, cactophilic yeasts are specific for this habitat, since it is a toxic environment for many organisms. The insect vectors are also specific, and responsible for the structure of the yeast communities in different cacti species. This study aimed to analyze the yeast communities associated to cacti in Brazilian ecosystems of Cerrado and Restinga, by comparing the yeast communities associated to cacti necrotic tissues, flowers and fruits, and the insects that frequent these plants. The samples were collected in the Parque Estadual do Sumidouro (Minas Gerais), in the city of Aurora do Tocantins (Tocantins) and in the Parque Nacional da Restinga de Jurubatiba (Rio de Janeiro). A total of 473 yeasts were obtained, with 91 isolates collected from Sumidouro, 209 isolates from Tocatins and 173 isolates from Restinga de Jurubatiba. The isolates were grouped according to their physiological and molecular profiles. The D1/D2 region of the large subunit rRNA gene of one isolate from each group was sequenced. The most frequent yeasts in cacti necrosis were Pichia cactophila, Candida (Ogataea) sonorensis and Sporopachydermia cereana complex. These species are known for being the most common cactophilic species, being found in several cacti species and in different regions. Candida (Kodamaea) restingae, Kodamaea nitidulidarum and Wickerhamiella cacticola were also isolated with great frequency, mainly from cacti flowers and from the intestine of larvae associated with this substrate. In addition, 20 possible new yeast species were isolated. Saccharomycetales sp. nov., a new species phylogenetically close to Candida nonsorbophila, was isolated in all the three regions in which the samples were collected, with 24 isolates occurring in necrotic tissues, flowers and fruits from different columnar cacti and from insects. The species Kluyveromyces marxianus similar differ by seven base pairs and one gap in the D1/D2 region from the species Kl. marxianus. This species was isolated with great frequency in necrotic tissues, flowers and fruits from the cactus Cereus saddianus, and from insects associated to necrosis in Micranthocereus dolichospermaticus in the region of Tocantins. In addition, this yeast was also isolated from the cactus Pilosocereus arrabidae, collected in the Restinga de Jurubatiba in Rio de Janeiro. Other potential new species were also isolated in the sampling performed in the Parque Nacional da Restinga de Jurubatiba. These were Candida xylopsoci similar, Erythrobasidium hasegawianum similar, Starmera pilosocereana sp. nov., Starmerella sp. and Yamadazyma sp.1. In the sampling performed in Aurora do Tocantins, four possible new species were also isolated, Pichia insulana similar, Wickerhamiella sp., Yamadazyma sp.2 and Yamadazyma sp.3. Meanwhile, in the Parque Estadual do Sumidouro the new species isolated were Barnettozyma sp., Bullera arundinariae similar, Candida montana similar, Cryptococcus flavus similar, Dipodascus australiensis similar, Kwoniella sp., Meira argovae similar, Sympodiomycopsis sp.1 and Sympodiomycopsis sp.2. This large number of new species points the need for continued studies of cactophilic yeasts from Brazilian ecosystems. Since few studies have been conducted in this area and in those researches the species identification was performed by solely physiological tests. This study showed that the yeast communities evaluated were more similar within the same region, and the community found in C. calcirupicola necrosis, in the Cerrado of Minas Gerais, was more similar to the Restinga ecosystem than to the Cerrado of Tocantins. This finding might be in accordance with the possibility of the yeast communities from C. calcirupicola and C. pernambucensis cacti share similar insect vectors species. Another hypothesis is that these cacti present similar chemical tissue composition, thus explaining the similarity among their yeast communities.